Development of Basic Electronics E-Modules Integrated with Problem Solving Models to Improve Students’ Mastery of Concepts and Creative Thinking - Frima Triani; Asrizal Asrizal (Postgraduate, University of Mataram, 2023)
In the 21st century, the Indonesian nation faces many global challenges. These demands include students having to have verbal and written communication skills, teamwork, creativity, research and problem solving skills to be able to compete in the future. To emphasize understanding and develop creative thinking, students need to be facilitated with tools that support learning. One of them is e-module. This research aims to determine the validity of basic electronics e-modules which are integrated with problem solving models to improve students' mastery of concepts and creative thinking. This research is Research and Development (R&D). Development is carried out by referring to the ADDIE model. The instrument used in this research is a basic electronics e-module validation sheet. The validity become evaluated the use of Aiken's V scale. Based on the results of basic electronics e-module validation data analysis, the average e-module validation value was 0.87. It can be concluded that the basic electronics e-module which is integrated with a problem solving model to improve students' mastery of concepts and creative thinking is declared valid and suitable for use